THE ROLE OF HOSPITAL MANAGEMENT IN RESOLUTION OF MEDICAL DISPUTES THROUGH MEDIATION PATHS IN THE HOSPITAL - Rangkutir, Rianiari; Risdawati, Irsyam; Zarzani N, T. Riza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
The legal relationship between medical personnel and patients in carrying out their services as health workers often results in incidents where health workers intentionally or unintentionally ignore the patient's rights until a problem or dispute arises. Mediation is a means of alternative dispute resolution outside of court. Medical malpractice is an action carried out by health workers regarding evil practices or not, in the case of failure to fulfill a standard that was initially determined by the profession. Regulations regarding the resolution of medical disputes through mediation are regulated in Article 29 of Law Number 36 of 2009, there are vague norms in it where the article regulates mediation but does not clearly explain what mediation is meant to be, more specifically it does not explain the penal mediation efforts involved. results in implicit in the settings, so it needs to be researched. PP No. 47 of 2021 CHAPTER III Hospital Obligations Article 27 paragraph (1) point r states that "preparing and implementing internal hospital regulations". This means that the law has mandated hospital management to create and establish their own rules regarding resolving disputes if a medical dispute occurs in the future. The method used in this research is a normative juridical research method where this is done by researching library materials or what is often said using secondary data in the form of positive law. The results of this discussion show that hospital management has established an initial mechanism for resolving medical disputes, namely mediation. As an alternative solution to problems in a very good and structured manner.